2019
DOI: 10.1177/0963689719885078
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Cell Tracking with Brighter and Red-Transferred Luciferase for Potential Application in Stem Cell Therapy

Abstract: This study investigated the safety of a novel cell-labeling technology with mKATE and Renilla reniformis luciferase (mKATE-renLUC) and assessed the efficacy on tracking implanted human placental stromal cells (PSC) in an erectile dysfunction (ED) animal model. Human PSC were labeled with mKATE-renLUC using a lentivirus. Cell viability, apoptosis, proliferation, migration, surface marker expression and differentiation potential of the labeled PSC were evaluated and compared with non-labeled PSC. The paracrine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…hPSC localization was first examined in an exploratory pilot cohort of 5 NEC-hPSC pups using dual-labeled hPSC for in vivo cell tracking and immunohistochemical analysis. As previously shown (36), hPSC were dual-tagged via lentiviral infection with a luciferase from Renilla reniformis (renLUC, for in vivo cell tracking) and mKATE (for IHC). NEC-hPSC pups received dual-labeled hPSC (referred to as mKATE hPSC) for the first cell injection (at 32 h) followed by untagged hPSC in the second cell injection.…”
Section: Placental Cell Localizationmentioning
confidence: 99%
See 2 more Smart Citations
“…hPSC localization was first examined in an exploratory pilot cohort of 5 NEC-hPSC pups using dual-labeled hPSC for in vivo cell tracking and immunohistochemical analysis. As previously shown (36), hPSC were dual-tagged via lentiviral infection with a luciferase from Renilla reniformis (renLUC, for in vivo cell tracking) and mKATE (for IHC). NEC-hPSC pups received dual-labeled hPSC (referred to as mKATE hPSC) for the first cell injection (at 32 h) followed by untagged hPSC in the second cell injection.…”
Section: Placental Cell Localizationmentioning
confidence: 99%
“…NEC-hPSC pups received dual-labeled hPSC (referred to as mKATE hPSC) for the first cell injection (at 32 h) followed by untagged hPSC in the second cell injection. For in vivo imaging on day 4, the luciferase substrate (Colenterazine 200 mg/kg) was intraperitoneally injected and in vivo imaging system (IVIS) images were obtained 5 min after substrate injection (36). An untreated NEC pup was used as an imaging control.…”
Section: Placental Cell Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioluminescence imaging visualizes photons emitted by luciferase enzyme reactions in live animals. To enable bioluminescence imaging, however, stem cells must be genetically modified to express the luciferase enzyme before transplantation [ 147 , 148 ] Stem cells can be labeled with nanoparticles such as superparamagnetic iron oxide nanoparticles, quantum dots, and pebbles in order to chase transplanted stem cells using MRI [ 149 , 150 , 151 ]. One study suggested the use of NSCs for the treatment of neurological diseases in a nonhuman primate stroke animal model.…”
Section: Imaging Techniques For Stem Cell Therapymentioning
confidence: 99%
“…However, the main application of RLuc is luciferase genetic reporter assay that has become an invaluable and routine tool for molecular biology research, including identification and characterization of protein functional variants [ 147 , 148 ], investigations of gene expression [ 148 , 149 , 150 ], transcription factors [ 151 , 152 , 153 , 154 , 155 ], receptor activity [ 156 ], miRNA expression [ 157 , 158 , 159 ], monitoring mRNA splicing events in cells [ 160 , 161 ], virus investigations [ 162 , 163 , 164 ], drug discovery [ 165 , 166 ], and identification and evaluation of virus inhibitors [ 167 , 168 ]. Moreover, RLuc is widely used for bioluminescence imaging of different processes in vivo [ 169 , 170 , 171 ] and guiding drug delivery to cells [ 172 , 173 ].…”
Section: Ctz-dependent Luciferase Analytical Applicationmentioning
confidence: 99%